Agriculture and food sector in Finland 2019 - (:unkn) unknown (Natural Resources Institute Finland, 2019)
The summer of 2018 will be remembered for the extreme weather conditions in Finland. The unusual heat and very small rainfall in North and Central Europe caused the worst drought in two decades. The impacts of drought on the agricultural sector were significant as many farmers lost at least part of their normal yield due to parched fields. The impact was the worst in the Nordic and Baltic countries. Hence, the summer was difficult for agricultural entrepreneurs, but there were also good news as the EU legislation reducing the occurrence of unfair trading practices (UTPs) in the food supply chain moved forward. The main objective of the Commission’s proposal published in April 2018 was ”to protect agricultural producers” because they are considered ”the weakest link” in the supply chain. Agreeing on the rules related to UTPs in the food supply chain was one of the important targets the current EU administration had set itself before the May 2019 elections. In 2019–2020, the farm policy agenda in Europe is likely to be dominated by reform proposals which are planned for the next period of the Common Agricultural Policy. On 1 June 2018, the Commission submitted its legislative proposals for the policy reform for 2021–2027. The proposals were created based on extensive stakeholder consultations during the past 18 months. Also, the withdrawal of the United Kingdom from the EU i.e. Brexit remains a central topic. The terms of future trade relations between the EU and the UK as well as the details of the withdrawal agreement are still open when writing this. The series of very complex negotiations, which lasted all year 2018, culminated in November in the withdrawal agreement between London and Brussels. However, it is still unclear if the deeply divided British Parliament can approve the negotiated agreement. The world food market was muddled up by the decisions of the US President Donald Trump whose trade war with China led to China placing tariffs for US agricultural products, such as soybeans. That is why the US has been seeking growing markets from Europe for soybean. The next pages present a short summary on the events of 2018 and a current outlook for what to expect from 2019. The special themes of this review highlight particularly organic production. The thematic articles discuss the development, structure, and environmental impacts of organic production as well as the world market prospects of organic products. Other special topics include the competitiveness of the Finnish meat chain, the investment development of agriculture, the ecosystem services of agriculture and the reform of the EU’s Common Agricultural Policy. We hope that our readers in and outside Finland will find this review useful.
Keywords: tuotanto; hinnat; kannattavuus; investoinnit; maatalous; luomutuotanto